2010
DOI: 10.1111/j.1600-0501.2010.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the nasopalatine canal and dental implant surgery: a radiographic analysis of 100 consecutive patients using limited cone-beam computed tomography

Abstract: The present study demonstrates decreasing values for the coronal width of the buccal bone wall in patients with missing central incisors and a time span since tooth loss of over 1 year. The age of the patients had a significant influence only on the length of the nasopalatine canal, with the mean values generally decreasing with an increasing age. The limited CBCT scans with FOVs varying between 4 × 4 and 8 × 8 cm are a valid diagnostic alternative to cross-sectional imaging in the anterior maxilla for dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
220
14
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(315 citation statements)
references
References 34 publications
60
220
14
21
Order By: Relevance
“…Authors previously described three shapes on the frontal plane ("I", "Y" and "II") [11]. In our study the "II" shape was not found.…”
Section: Resultscontrasting
confidence: 61%
“…Authors previously described three shapes on the frontal plane ("I", "Y" and "II") [11]. In our study the "II" shape was not found.…”
Section: Resultscontrasting
confidence: 61%
“…The oral opening of the NPC, the incisive foramen, is found in this region which maintains close proximity to the roots of the upper central incisors [4] [5]. In view of this anatomical relationship, thorough radiographic analysis is necessary during dental implant planning [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…4,5) The mean antero-posterior angulation at the inferior level was 75.3 degrees in IIIC, and the value was close to that of adults (mean: 74.3 degrees) in a previous study. 4) The mean difference of angulation between the inferior and middle levels was lower in IIA and IIC, and it was understood that the maxillary incisive canal was straight from the inferior level to nasal floor.…”
Section: Discussionmentioning
confidence: 66%
“…[1][2][3] The diameter and angulation to the palatal plane of the maxillary incisive canal in adults were reported in previous studies using spiral and cone-beam computed tomography (CT). [4][5][6] However, development of the maxillary incisive canal in childhood was not evaluated.…”
Section: Introductionmentioning
confidence: 99%